A preliminary study of the physico-chemical properties and fatty acid profile of five palm oil genotypes cultivated in Northeast of Brazil - Araújo, Katarynna Santos de; Silva, Sérvulo Mercier Siqueira e; Santos, Leonardo Devilles dos; Malafaia, Carolina Barbosa; Barbosa, Mariana Oliveira (Journal of Environmental Analysis and Progress, 2019)
The palm oil (Elaeis guineensis Jacq.) is widely produced in the Brazilian Amazon region; however, the expansion of its cultivation to other environments is mandatory to attend the increasing demand of the industry, especially in the food and biodiesel fields. This study aimed to analyze the lipid profile and physicochemical characteristics of crude palm oil obtained from different palm genotypes cultivated in Goiana-PE, Northeast of Brazil. All genotypes showed high oil yield (> 60%). Lipid profile showed that the palmitic and linoleic acids were predominant in the oil (about 80%). Iodine and saponification index ranged from 50.2 to 55.3g I2.100 g-1 and 184.3 to 185.4 mg KOH.g-1 of oil, respectively. Saponification and iodine levels also showed similar values among the studied genotypes. Acid and peroxide indexes presented values within the National Health Surveillance Agency (ANVISA). BRS C7201 genotype presented more attractive and viable results for its cultivation and development in the studied area.